Training in first aid in active tourism - Carrillo Heredia, MJ. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
There is an increasing demand in the active tourism sector in Spain, which offers activities that imply certain deliberately accepted risks. Although risks are minimized by the broad technical skills of sector workers, accidents might happen. Due to lack of consensus legal regulations in Spain, this article focus on to compare the requirements demanded by each community and reflect on the first aid training level that active tourism instructors, guides, and monitors have in Spain. Key words: active tourism, first aid, training.